2012
DOI: 10.1088/1674-1056/21/9/094101
|View full text |Cite
|
Sign up to set email alerts
|

A novel structure for a broadband left-handed metamaterial

Abstract: A low absorptivity broadband negative refractive index metamaterial with a multi-gap split-ring and metallic cross (MSMC) structure is proposed and investigated numerically and experimentally in the microwave frequency range. The effective media parameters were retrieved from the numerical and experimental results, which clearly show that there exists a very wide frequency band where the permittivity and permeability are negative. The influence of the structure parameters on the magnetic response and the cut-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…[24][25][26] Metamaterials have received much attention recently because of their fascinating properties. [27][28][29][30][31][32] They can basically be divided into two types: one is a single-negative (SNG) material with negative permittivity or permeability, the other is a double-negative (DNG) material with negative permittivity and permeability. There are two types of SNG materials, the one with negative permittivity (ε < 0, µ > 0) is called an epsilon-negative (ENG) material, and the one with negative permeability (µ < 0, ε > 0) is called an mu-negative (MNG) material.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] Metamaterials have received much attention recently because of their fascinating properties. [27][28][29][30][31][32] They can basically be divided into two types: one is a single-negative (SNG) material with negative permittivity or permeability, the other is a double-negative (DNG) material with negative permittivity and permeability. There are two types of SNG materials, the one with negative permittivity (ε < 0, µ > 0) is called an epsilon-negative (ENG) material, and the one with negative permeability (µ < 0, ε > 0) is called an mu-negative (MNG) material.…”
Section: Introductionmentioning
confidence: 99%
“…The transmission properties of two-dimensional (2D) hole arrays perforated in metal-dielectric-metal (MDM) metamaterials of subwavelength apertures have become a very active research area in electromagnetism since extraordinary optical transmission (EOT) was reported by Ebbesen et al [1] Over the past decade, the EOT and negative refractive index (NRI) of 2D hole arrays of sandwiched metamaterials have been widely investigated because of their remarkable properties. [2][3][4][5][6][7][8][9] Very recently, many experiments have been conducted to study the influence of hole shape on the optical transmission properties of 2D hole arrays. [10][11][12] But unfortunately in these experimental studies, the role of shape in determining the NRI of 2D hole arrays of sandwiched metamaterials was not taken into consideration, nor was what shape of hole should be used to obtain better transmittance and NRI.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18] Recently, it has been reported that terahertz metamaterials exhibit single-band and dual-band responses. [19][20][21][22][23][24] General symmetric and asymmetric triple-resonant metamaterials as the extension of dual-band and single-band structures are also presented. [25,26] However, these structures are laterally designed structures that have difficulty in constructing multiresonance (more than five resonances).…”
Section: Introductionmentioning
confidence: 99%